A Hyper-Attenuated Variant of Rift Valley Fever Virus Generated by a Mutagenic Drug (Favipiravir) Unveils Potential Virulence Markers - Borrego, Belén; Brun, Alejandro (Frontiers in Microbiology, 2021)
Rift Valley fever virus (RVFV) is a mosquito-borne bunyavirus that causes Rift Valley fever (RVF), a zoonotic disease of wild and domestic ruminants, causing serious economic losses and a threat to human health that could be controlled by vaccination. Though RVF vaccines are available for livestock, no RVF vaccines have been licensed for veterinary use in non-endemic countries nor for human populations in RVF risk areas. In a recent work, we showed that favipiravir, a promising drug with antiviral activity against a number of RNA viruses, led to the extinction of RVFV from infected cell cultures. Nevertheless, certain drug concentrations allowed the recovery of a virus variant showing increased resistance to favipiravir. In this work, we characterized this novel resistant variant both at genomic and phenotypic level in vitro and in vivo. Interestingly, the resistant virus displayed reduced growth rates in C6/36 insect cells but not in mammalian cell lines, and was highly attenuated but still immunogenic in vivo. Some amino acid substitutions were identified in the viral RNA-dependent RNA-polymerase (RdRp) gene and in the virus encoded type I-interferon (IFN-I) antagonist NSs gene, in catalytic core motifs and nuclear localization associated positions, respectively. These data may help to characterize novel potential virulence markers, offering additional strategies for further safety improvements of RVF live attenuated vaccine candidates.